Positive sodium supplementing agent NaxFeyNizO4 (at) C, preparation method thereof and application of positive sodium supplementing agent NaxFeyNizO4 (at) C in sodium ion battery

By preparing NaxFeyNizO4@C positive electrode sodium supplementation agent, the existing positive electrode sodium supplementation agent is easily produced and the sodium supplementation effect is poor, and the high energy density and good cycle stability of sodium ion batteries are achieved.

CN119581707APending Publication Date: 2025-03-07福建龙净储能电池有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411746875.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing positive electrode sodium supplementation agents are prone to gas production when used, and the sodium supplementation effect is poor, resulting in low energy density of sodium ion batteries and poor capacity performance and cycle stability.

Method used

NaxFeyNizO4@C is used as the positive electrode sodium supplement agent. By mixing the sodium source, iron source, nickel source and organic solvent and calcining, the compound NFNC is obtained, and then mixed with the carbon source to calcinate, to prepare a positive electrode sodium supplement agent with low gas yield and high stability.

Benefits of technology

This positive electrode sodium supplementation agent significantly reduces gas production in sodium ion batteries, improves discharge capacity and cycling performance, and has good structural stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163957960000111
    Figure BDA0005163957960000111
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and relates to a positive electrode sodium supplementing agent NaxFeyNizO4 (at) C, a preparation method thereof and an application of the positive electrode sodium supplementing agent NaxFeyNizO4 (at) C in a sodium ion battery. The preparation method of the positive electrode sodium supplementing agent comprises the following steps: S1, mixing a sodium source, an iron source, a nickel source and an organic solvent, and calcining to obtain a compound NFNC; and S2, the compound NFNC obtained in the step S1 and a carbon source are mixed and calcined to obtain the positive sodium supplement NaxFeyNizO4 (at) C, and x: y: z = (2-4): (0.5-2): 1. The preparation method is characterized in that a sodium source, an iron source, a nickel source and an organic solvent are mixed and then subjected to first calcination treatment to obtain a compound NFNC, and then the compound NFNC and a carbon source are mixed and then subjected to second calcination treatment, so that the obtained positive electrode sodium supplementing agent NaxFeyNizO4 (at) C can reduce gas production of a sodium ion battery after a formation stage; and the sodium ion battery has excellent discharge capacity and cycle performance in a working voltage range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and particularly relates to a positive electrode sodium supplement Na x Fe y Ni z O4@C, its preparation method and application in sodium ion batteries. Background Art

[0002] At present, sodium-ion batteries have become a research hotspot in energy storage technology due to their abundant resources and low prices. However, during the initial charge and discharge process of sodium-ion batteries, the positive electrode cracks due to oxygen evolution, CEI film forms on the surface, and SEI film forms on the surface of the negative electrode hard carbon, resulting in irreversible capacity loss of more than 8%, and active sodium ions are continuously and irreversibly consumed during the cycle. All these have led to the low energy density of sodium-ion batteries, limiting their applicability in high energy density scenarios.

[0003] In order to solve the disadvantage of low energy density of sodium ions, the more mature research directions are mainly negative electrode sodium supplementation and positive electrode sodium supplementation. Among them, the methods of negative electrode sodium supplementation are mainly: (1) short-circuit sodium supplementation, which is generally to directly contact the negative electrode sheet of the sodium ion battery with sodium metal or sodium foil by solution infiltration and mechanical rolling. This method is simple and effective, but due to the strong activity of sodium metal, a strict anhydrous and oxygen-free environment is required during the preparation or storage process, which has safety risks; (2) adding stabilized sodium metal powder can compensate for the active sodium ions consumed in the first cycle of the negative electrode material and improve the energy density, but how to use metallic sodium stably is also an urgent problem to be solved; (3) electrochemical pre-sodiumization, the negative electrode sheet to be treated and the sodium metal sheet are prepared into a half-cell, and the sodium ions are pre-embedded into the negative electrode active material by constant current and constant voltage discharge. However, the steps in the assembly of the half-cell are complicated, and a large amount of waste liquid and waste gas are easily generated, which poses a safety hazard and cannot be used on a large scale. Compared with the negative electrode, which requires an additional process for sodium replenishment, the positive electrode sodium replenishment method is extremely simple and flexible. It mainly achieves the replenishment of active sodium during the first and cycle processes of the sodium ion battery by adding a sodium replenisher during the positive electrode homogenization process. However, there are the following problems when using positive electrode sodium replenishers: First, the decomposition of the sodium replenisher itself will produce a large amount of gas, causing the positive electrode material and the current collector to peel off, seriously affecting the safety performance of the sodium ion battery; second, the general positive electrode sodium replenisher has a strong redox property, and an irreversible phase change occurs, resulting in too low efficiency of sodium replenishment, which has limited improvement on battery performance. Therefore, it is urgent to develop a positive electrode sodium replenisher with low gas production, good stability, excellent sodium replenishment effect, and simple process. Summary of the invention

[0004] The purpose of the present invention is to provide a positive electrode sodium supplement agent Na to address the shortcomings of the existing positive electrode sodium supplement agent, which is easy to produce gas and has poor sodium supplement effect, and has limited effect on improving the capacity performance of sodium ion batteries.x Fe y Ni z O4@C and its preparation method and application in sodium ion batteries, the positive electrode sodium supplement Na x Fe y Ni z O4@C has the characteristics of low gas production and good stability, which helps to improve the energy density of sodium-ion batteries, making the positive electrode sodium supplement Na x Fe y Ni z O4@C sodium-ion batteries have good capacity performance and cycle stability.

[0005] In the first aspect, the present invention provides a positive electrode sodium supplement Na x Fe y Ni z Preparation method of O4@C, the positive electrode sodium supplement Na x Fe y Ni z The preparation method of O4@C comprises the following steps: S1. a sodium source, an iron source, a nickel source, and an organic solvent are subjected to a first mixing treatment and then filtered, and then a precursor mixture obtained after separation of the organic solvent is subjected to a first calcination treatment to obtain a compound NFNC; S2. the compound NFNC obtained in step S1 is mixed with a carbon source and then subjected to a second calcination treatment to obtain a positive electrode sodium supplement Na x Fe y Ni z O4@C, where x:y:z=(2~4):(0.5~2):1.

[0006] In a preferred embodiment, the positive electrode sodium supplement Na x Fe y Ni z The Dv50 particle size of O4@C is 0.5~3μm.

[0007] In a preferred embodiment, the molar ratio of the sodium source, the iron source and the nickel source is (2-5):(0.5-3):1.

[0008] In a preferred embodiment, the ratio between the mass of the sodium source, the iron source, and the nickel source and the volume of the organic solvent is 1 kg: (0.4-0.7) L.

[0009] In a preferred embodiment, the sodium source is selected from at least one of sodium oxide, sodium peroxide, sodium carbonate, sodium hydroxide, sodium chloride, sodium nitrate and sodium oxalate.

[0010] In a preferred embodiment, the iron source is selected from at least one of ferrous sulfate, ferrous phosphate, ferrous carbonate, ferric chloride and ferric nitrate.

[0011] In a preferred embodiment, the nickel source is selected from at least one of nickel oxide, nickel hydroxide, nickel sulfate, nickel oxalate, sodium nitrate and nickel chloride.

[0012] In a preferred embodiment, the organic solvent is a fat-soluble solvent.

[0013] In a preferred embodiment, the fat-soluble solvent is selected from at least one of ether, petroleum ether, kerosene, hexane, heptane and carbon tetrachloride.

[0014] In a preferred embodiment, the mass ratio of the compound NFNC to the carbon source is 1:(0.3-0.4).

[0015] In a preferred embodiment, the carbon source is selected from at least one of glucose, sucrose, asphalt, cellulose and citric acid.

[0016] In a preferred embodiment, in step S1, the first mixing treatment is performed in the following manner: a sodium source, an iron source, a nickel source, and an organic solvent are placed in a ball milling jar for ball milling.

[0017] In a preferred embodiment, in step S1, the conditions of the ball milling treatment include: a rotation speed of 300 to 400 rpm and a time of 6 to 8 hours.

[0018] In a preferred embodiment, in step S1, the conditions of the first calcination treatment include: temperature T1 is 350-400°C, and holding time t1 is 3-5h.

[0019] In a preferred embodiment, in step S2, the mixing treatment is performed in the following manner: placing the compound NFNC and the carbon source in a fusion coating machine for coating treatment.

[0020] In a preferred embodiment, the coating treatment conditions include: a rotation speed of 500 to 800 rpm and a time of 2 to 3 hours.

[0021] In a preferred embodiment, in step S2, the conditions of the second calcination treatment include: temperature T2 is 900-1100° C., and holding time t2 is 4-6 h.

[0022] In a second aspect, the present invention provides a positive electrode sodium supplement Na prepared by the above method. x Fe y Ni z O4@C.

[0023] In a preferred embodiment, the positive electrode sodium supplement Na x Fey Ni z The Dv50 particle size of O4@C is 0.5~3μm.

[0024] In a third aspect, the present invention also provides the above-mentioned positive electrode sodium supplement Na x Fe y Ni z Application of O4@C in sodium-ion batteries.

[0025] The key to the present invention is to firstly mix the sodium source, the iron source, the nickel source and the organic solvent and then filter, perform a first calcination treatment to obtain the compound NFNC, and then mix the compound NFNC with the carbon source and perform a second calcination treatment to obtain the positive electrode sodium supplement Na x Fe y Ni z O4@C, the positive electrode sodium supplement Na x Fe y Ni z O4@C has good structural stability. Adding this positive electrode sodium supplement to the positive electrode slurry of the sodium ion battery can reduce the gas production of the sodium ion battery after the formation stage, and the sodium ion battery has excellent discharge capacity and cycle performance within the operating voltage range. The possible reason is that the introduced Fe and Ni can increase the redox potential of the positive electrode sodium supplement and synergistically enhance the structural stability of the positive electrode sodium supplement, so that within the operating voltage range of the sodium ion battery, the positive electrode sodium supplement Na x Fe y Ni z O4@C can release more active sodium ions, which is beneficial to improve the energy density of sodium ion batteries, thus having excellent discharge capacity and cycle performance. In addition, the positive electrode sodium supplement is chemically inert after releasing sodium ions, which reduces the occurrence of chemical side reactions and reduces gas production. x Fe y Ni z O4@C includes sodium-supplementing compounds Na x Fe y Ni z O4 and carbon material substrate, sodium supplement compound Na x Fe y Ni z O4 is evenly distributed on the surface and / or pores of the carbon material, x Fe y Ni z When O4@C is applied to the positive electrode of a sodium ion battery, the carbon material can build a conductive network between the sodium supplement compound and the positive electrode active material, which is beneficial to enhancing the conductivity of the positive electrode and reducing the occurrence of side reactions of the positive electrode, thereby improving the capacity performance and cycle stability of the sodium battery. xFe y Ni z O4@C produces less gas when used in sodium-ion batteries and can significantly improve the discharge capacity and cycle performance of sodium-ion batteries. The preparation method is simple, does not require strict environmental requirements, is highly safe, and has good application prospects. DETAILED DESCRIPTION

[0026] The positive electrode sodium supplement Na provided by the present invention x Fe y Ni z The preparation method of O4@C comprises the following steps: S1. a sodium source, an iron source, a nickel source, and an organic solvent are subjected to a first mixing treatment and then subjected to a first calcination treatment to obtain a compound NFNC; S2. the compound NFNC obtained in step S1 and a carbon source are subjected to a second mixing treatment and then subjected to a second calcination treatment to obtain a positive electrode sodium supplement Na x Fe y Ni z O4@C, wherein x:y:z=(2~4):(0.5~2):1. When z is 1, x is 2~4, such as 2, 2.5, 3, 3.5, 4 or any value therebetween, and y is 0.5~2, such as 0.5, 0.8, 1, 1.5, 2 or any value therebetween.

[0027] In the present invention, the positive electrode sodium supplement Na x Fe y Ni z The Dv50 particle size of O4@C is preferably 0.5-3 μm, such as 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or any value therebetween. Within the above preferred range, it is more conducive to the positive electrode sodium supplement Na x Fe y Ni z O4@C is dispersed between the particles of the positive electrode active material, enhancing the conductivity of the positive electrode sheet and reducing the resistance, which is more conducive to the capacity performance of the sodium ion battery and improving the discharge capacity and cycle performance. The term "Dv50" refers to the particle size corresponding to the cumulative volume distribution reaching 50% in the particle size distribution.

[0028] In the present invention, the molar ratio of the sodium source, the iron source, and the nickel source is preferably (2-5): (0.5-3): 1. Controlling the molar ratio of the sodium source, the iron source, and the nickel source within the above preferred range is more conducive to increasing the positive electrode sodium supplement Na x Fe y Ni zThe sodium content of O4@C releases more active sodium ions, improves the energy density of sodium ion batteries, and thus improves the capacity performance and cycle performance. On the other hand, it is more conducive to Fe and Ni to synergistically improve the structural stability of the positive electrode sodium supplement and reduce gas production. Taking the molar number of the nickel source as 1 mol, the molar number of the sodium source is preferably 2 to 5 mol, such as 2 mol, 3 mol, 4 mol, 5 mol or any value therebetween; the molar number of the iron source is preferably 0.5 to 3 mol, such as 0.5 mol, 0.6 mol, 0.8 mol, 1 mol, 1.2 mol, 1.5 mol, 2 mol, 3 mol or any value therebetween.

[0029] In the present invention, the ratio between the mass of the sodium source, iron source and nickel source and the volume of the organic solvent is preferably 1kg:(0.4-0.7)L, such as 1kg:0.4L, 1kg:0.5L, 1kg:0.6L, 1kg:0.7L or any value therebetween.

[0030] In the present invention, the specific types of the sodium source, iron source, and nickel source are not limited, as long as they can provide a class of compounds of sodium element, iron element, and nickel element respectively. Specific examples of the sodium source include, but are not limited to, at least one of sodium oxide, sodium peroxide, sodium carbonate, sodium hydroxide, sodium chloride, sodium nitrate, and sodium oxalate. Specific examples of the iron source include, but are not limited to, at least one of ferrous sulfate, ferrous phosphate, ferrous carbonate, ferric chloride, and ferric nitrate. Specific examples of the nickel source include, but are not limited to, at least one of nickel oxide, nickel hydroxide, nickel sulfate, nickel oxalate, sodium nitrate, and nickel chloride.

[0031] In the present invention, the organic solvent may be an organic solvent conventionally used in the art, and specific examples thereof include, but are not limited to, at least one of dimethyl sulfoxide, dimethylformamide, methanol, acetonitrile, ether, petroleum ether, kerosene, hexane, heptane and carbon tetrachloride. The main function is to enable the sodium source, iron source and nickel source to be uniformly mixed and isolated from the air, which is conducive to the subsequent acquisition of a positive electrode sodium supplement with good morphological consistency, thereby stabilizing the consistency and cycle stability of the sodium ion battery capacity of the positive electrode sodium supplement. The organic solvent is preferably a fat-soluble solvent, and specific examples thereof include, but are not limited to, at least one of ether, petroleum ether, kerosene, hexane, heptane and carbon tetrachloride. The use of a fat-soluble solvent is more conducive to providing a homogeneous reaction environment, preventing the sodium source, iron source and nickel source from reacting with air to produce side reactions during ball milling, allowing the sodium source, iron source and nickel source to be fully mixed and uniform, and at the same time, the good thermal conductivity of the fat-soluble solvent can also prevent overheating problems during material mixing. The term "fat-soluble solvent" refers to a class of organic solvents having non-polarity or weak polarity.

[0032] In the present invention, the mass ratio of the compound NFNC to the carbon source is preferably 1:(0.3-0.4), such as 1:0.3, 1:0.32, 1:0.35, 1:0.38, 1:0.4 or any value therebetween. Controlling the mass ratio of the compound NFNC to the carbon source within the above preferred range is more conducive to improving the coating uniformity of the compound NFNC and the carbon source, and improving the positive electrode sodium supplement Na x Fe y Ni z The electronic conductivity of O4@C and the chemical inertness after sodium supplementation improve the positive electrode sodium supplement Na x Fe y Ni z Capacity performance and cycle stability of sodium ion batteries of O4@C. Specific examples of the carbon source include, but are not limited to, at least one of glucose, sucrose, asphalt, cellulose and citric acid.

[0033] In the present invention, in step S1, the first mixing treatment is preferably carried out in the following manner: placing a sodium source, an iron source, a nickel source, and an organic solvent in a ball mill for ball milling. The conditions for the ball milling treatment may specifically include: a rotation speed of preferably 300 to 400 rpm, such as 300 rpm, 320 rpm, 350 rpm, 380 rpm, 400 rpm, or any value therebetween; and a time of preferably 6 to 8 hours, such as 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, or any value therebetween.

[0034] In the present invention, in step S1, the conditions of the first calcination treatment may specifically include: the temperature T1 is preferably 350-400°C, such as 350°C, 360°C, 370°C, 380°C, 390°C, 400°C or any value therebetween; the holding time t1 is preferably 3-5h, such as 3h, 3.5h, 4h, 4.5h, 5h or any value therebetween. The conditions of the first calcination treatment may also include: the heating rate V1 is preferably 3-5°C / min, such as 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min or any value therebetween. The first calcination treatment is preferably carried out under an inert gas atmosphere. The inert gas is preferably at least one selected from nitrogen, argon, xenon, helium and neon.

[0035] In the present invention, in step S2, the second mixing treatment is preferably carried out in the following manner: placing the compound NFNC and the carbon source in a fusion coating machine for coating treatment. The coating treatment conditions may specifically include: the rotation speed is preferably 500-800 rpm, such as 500 rpm, 600 rpm, 700 rpm, 800 rpm or any value therebetween; the time is preferably 2-3 h, such as 2 h, 2.2 h, 2.5 h, 2.8 h, 3 h or any value therebetween.

[0036] In the present invention, in step S2, the conditions of the second calcination treatment may specifically include: the temperature T2 is preferably 900-1100°C, such as 900°C, 950°C, 1000°C, 1050°C, 1100°C or any value therebetween; the holding time t2 is preferably 4-6h, such as 4h, 4.5h, 5h, 5.5h, 6h or any value therebetween. The conditions of the second calcination treatment may also include: the heating rate V2 is preferably 1-3°C / min, such as 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min or any value therebetween. The second calcination treatment is preferably carried out under an inert gas atmosphere. The inert gas is preferably at least one selected from nitrogen, argon, xenon, helium and neon.

[0037] The present invention will be described in detail below through specific embodiments.

[0038] Example 1 Positive electrode sodium supplement Na x Fe y Ni z Preparation of O4@C

[0039] S1. 5.00 kg of sodium peroxide (64.12 mol), 4.87 kg of ferrous sulfate (32.06 mol), 2.39 kg of nickel oxide (32.06 mol) and 7.36 L of ether solvent were placed in a planetary ball mill, and the conditions were set as follows: the speed was 300 rpm and the time was 6 h. After the high-energy ball milling was completed, the unreacted residue in the precursor was filtered out through a 30-mesh screen, and the obtained filtrate was subjected to high-temperature solvent recovery to obtain a precursor mixture, and the precursor mixture was placed in a box-type atmosphere furnace for calcination, and the conditions were set as follows: the temperature T1 was 350 ° C, the heating rate V1 was 3 ° C / min, the holding time t1 was 3 h, and the protective atmosphere was nitrogen, to obtain the compound NFNC;

[0040] S2. Compound NFNC and glucose were placed in a fusion coating machine at a mass ratio of 1:0.3 for coating treatment. The conditions were set as follows: the rotation speed was 500 rpm and the time was 3 h. Then it was placed in a box-type atmosphere furnace for calcination. The conditions were set as temperature T2 of 900 ° C, heating rate V2 of 1 ° C / min, insulation time t2 of 4 h, and protective atmosphere of nitrogen. The calcined product was sieved to obtain a positive electrode sodium supplement Na with a particle size of 1.5 μm at Dv50. x Fe y Ni z O4@C, where x:y:z=2:1:1.

[0041] Example 2 Positive electrode sodium supplement Na x Fe y Ni z Preparation of O4@C

[0042] S1. 4.00 kg of sodium carbonate (37.74 mol), 1.14 kg of iron phosphate (7.55 mol), 1.40 kg of nickel hydroxide (15.10 mol) and 3.27 L of petroleum ether solvent were placed in a planetary ball mill, and the conditions were set as follows: the speed was 350 rpm and the time was 7 h. After the high-energy ball milling was completed, the unreacted residue in the precursor was filtered out through a 30-mesh screen, and the obtained filtrate was subjected to high-temperature solvent recovery to obtain a precursor mixture, and the precursor mixture was placed in a box-type atmosphere furnace for calcination, and the conditions were set as follows: the temperature T1 was 380°C, the heating rate V1 was 4°C / min, the holding time t1 was 4 h, and the protective atmosphere was nitrogen to obtain the compound NFNC;

[0043] S2. Compound NFNC and glucose were placed in a fusion coating machine at a mass ratio of 1:0.35 for coating treatment. The conditions were set as follows: the rotation speed was 600 rpm and the time was 2.5 h. Then it was placed in a box-type atmosphere furnace for calcination. The conditions were set as temperature T2 of 1000 ° C, heating rate V2 of 2 ° C / min, insulation time t2 of 5 h, and protective atmosphere of nitrogen. The calcined product was sieved to obtain a positive electrode sodium supplement Na with a particle size of 2 μm at Dv50. x Fe y Ni z O4@C, where x:y:z=2.5:0.5:1.

[0044] Example 3 Positive electrode sodium supplement Na x Fe y Ni z Preparation of O4@C

[0045] S1. 3.00 kg of sodium hydroxide (75.00 mol), 4.35 kg of ferrous carbonate (37.50 mol), 2.75 kg of nickel oxalate (18.75 mol) and 5.73 L of kerosene solvent were placed in a planetary ball mill, and the conditions were set as follows: the speed was 400 rpm and the time was 5 h. After the high-energy ball milling was completed, the unreacted residue in the precursor was filtered out through a 30-mesh screen, and the obtained filtrate was subjected to high-temperature solvent recovery to obtain a precursor mixture, and the precursor mixture was placed in a box-type atmosphere furnace for calcination, and the conditions were set as follows: the temperature T1 was 400 ° C, the heating rate V1 was 5 ° C / min, the holding time t1 was 5 h, and the protective atmosphere was nitrogen to obtain the compound NFNC;

[0046] S2. Compound NFNC and glucose were placed in a fusion coating machine at a mass ratio of 1:0.4 for coating treatment. The conditions were set as follows: the speed was 800 rpm and the time was 2 h. Then it was placed in a box-type atmosphere furnace for calcination. The conditions were set as temperature T2 of 1100 ° C, heating rate V2 of 3 ° C / min, insulation time t2 of 6 h, and protective atmosphere of nitrogen. The calcined product was sieved to obtain a positive electrode sodium supplement Na with a particle size of 3 μm at Dv50. x Fe y Ni z O4@C, where x:y:z=4:2:1.

[0047] Example 4 Positive Electrode Sodium Supplement Na x Fe y Ni z Preparation of O4@C

[0048] Prepare the positive electrode sodium supplement Na according to the method of Example 1 x Fe y Ni z O4@C, except that in step S1, the same volume of dimethyl sulfoxide was used instead of ether, and the other conditions were the same, thereby preparing the positive electrode sodium supplement Na x Fe y Ni z O4@C, where x:y:z=2:1:1.

[0049] Comparative Example 1 Preparation of Reference Positive Electrode Sodium Supplement

[0050] The reference positive electrode sodium supplement was prepared according to the method of Example 1, except that the same mole of ferrous sulfate was used instead of nickel oxide in step S1, and the other conditions were the same, thereby preparing the reference positive electrode sodium supplement Na x Fe y O4@C, where x:y=2:1.5.

[0051] Comparative Example 2 Preparation of Reference Positive Electrode Sodium Supplement

[0052] The reference positive electrode sodium supplement was prepared according to the method of Example 1, except that the same mole of nickel oxide was used instead of ferrous sulfate in step S1, and the other conditions were the same, thereby preparing the reference positive electrode sodium supplement Na x Ni z O4@C, where x:z=2:1.6.

[0053] Comparative Example 3 Preparation of Reference Positive Electrode Sodium Supplement

[0054] The reference positive electrode sodium supplement was prepared according to the method of Example 1, except that the same volume of pure water was used instead of ether in step S1, and the other conditions were the same, thereby preparing the reference positive electrode sodium supplement Na x Fe y Ni z O4@C, where x:y:z=1:0.8:1.

[0055] Comparative Example 4 Preparation of Reference Positive Electrode Sodium Supplement

[0056] S1. 5.00 kg of sodium peroxide (64.12 mol), 4.87 kg of ferrous sulfate (32.06 mol), 2.39 kg of nickel oxide (32.06 mol) and 7.36 L of ether solvent were placed in a planetary ball mill, and the conditions were set as follows: the speed was 300 rpm and the time was 6 h. After the high-energy ball milling was completed, the mixture was placed in a box-type atmosphere furnace for calcination, and the conditions were set as follows: the temperature T1 was 350 ° C, the heating rate V1 was 3 ° C / min, the holding time t1 was 3 h, and the protective atmosphere was nitrogen, to obtain the compound NFNC;

[0057] S2. The compound NFNC was placed in a box-type atmosphere furnace for calcination. The conditions were set to a temperature of 900°C, a heating rate of 1°C / min, a holding time of 4h, and a nitrogen atmosphere. The calcined product was sieved to obtain a reference positive electrode sodium supplement Na with a Dv50 particle size of 1.5 μm. x Fe y Ni z O4, where x:y:z=2:1:1.

[0058] Test Case

[0059] The positive electrode sodium supplement prepared in the above examples and comparative examples was added to the positive electrode sheet according to the following method, and assembled with the negative electrode sheet, electrolyte, and separator to obtain a sodium ion soft-pack battery, and the gas production performance, discharge capacity performance, and cycle performance were tested. The results are shown in Table 1.

[0060] (1) Assembly of sodium-ion soft-pack batteries

[0061] ① Preparation of sodium-supplemented positive electrode sheet: The positive electrode active material of the sodium ion battery is mixed with the positive electrode sodium supplement Na x Fe y Ni z O4@C was batch mixed at a mass ratio of 100:5, and then the batch mixed positive electrode active material was mixed with positive electrode conductive paste (graphene@carbon nanotube composite conductive paste), positive electrode conductive agent carbon black (Super-P), and positive electrode binder (polyvinylidene fluoride, PVDF) at a mass ratio of 94:2:2:2, and solvent N-methylpyrrolidone (NMP) was added in a planetary vacuum mixer, and mixed by a dry process to obtain positive electrode slurry, and the positive electrode slurry was coated on both sides of aluminum foil, and a positive electrode sheet with a length × width × thickness of 70 mm × 50 mm × 150 μm (± 2 μm) was obtained by drying, rolling, cutting, and die-cutting; according to the above method, no positive electrode sodium supplement Na was added x Fe y Ni z O4@C, thus preparing the positive electrode sheet of the blank example.

[0062] ② Preparation of negative electrode sheet: Sodium ion battery negative electrode active material, negative electrode conductive agent carbon black (Super-P), negative electrode binder 1 (sodium carboxymethyl cellulose), binder 2 (styrene-butadiene rubber) are mixed in a mass ratio of 92:2:3:3, deionized water is added and mixed in a planetary vacuum mixer to obtain negative electrode slurry, and the negative electrode slurry is evenly coated on both sides of aluminum foil, and a negative electrode sheet with a length × width × thickness of 75 mm × 53 mm × 110 μm (± 2 μm) is obtained by drying, rolling, cutting, and die cutting;

[0063] ③ Preparation of electrolyte: In a dry room with an air dew point of -50°C, ethylene carbonate (EC), propylene carbonate (PC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:1:1. The sodium salt is sodium hexafluorophosphate NaPF6 with a concentration of 1 mol / L. 2% of vinylene carbonate (VC) and 1% of fluoroethylene carbonate (FEC) are added as additives. After magnetic stirring, the electrolyte is prepared.

[0064] ④ Selection of diaphragm: The diaphragm is prepared with polyethylene (PE) as the base film and aluminum oxide as the coating layer.

[0065] ⑤ Soft-pack battery assembly: The sodium-supplemented positive electrode sheet, negative electrode sheet and diaphragm prepared above are dried, and after the moisture content reaches the standard, they are assembled into bare cells through a lamination process. After welding the positive and negative electrode tabs, they are loaded into a battery shell with an aluminum-plastic film, and the prepared electrolyte is injected. The finished soft-pack battery is obtained through the steps of sealing, high-temperature standing, formation, and secondary sealing. The positive electrode sheet without the addition of the sodium supplement agent is assembled according to the above method to obtain a soft-pack battery as a blank example.

[0066] (2) Battery formation gas production test: The sodium ion soft-pack battery prepared above was placed in an in-situ multi-channel storage gas production test system. The Nebula test system is a charging and discharging device. The formation test conditions are as follows: ① Standing at a high temperature of 45℃±2℃ for 120min, charging to 3V at a constant current of 0.05C, and then charging to 3.95V at a constant current of 0.2C, with a cut-off current of 0.05C; ② Standing for 10min after charging, discharging to 2V at a constant current of 1C, and recording the discharge capacity of the sodium ion battery; In the storage gas production test system, the buoyancy change of the sodium battery during the charging and discharging process is monitored in real time, converted into a gas volume change, and the total amount of gas generated by the sodium ion battery in the formation stage is calculated;

[0067] (3) Battery electrical performance test: The test system is the Nebula test system. The electrochemical performance of the sodium ion soft-pack battery prepared above is tested according to the following method: ① The first coulomb efficiency test is carried out at room temperature 25℃±2℃, charging to 4.0V with a constant current of 0.1C, the cut-off current is 0.05C, and the battery is left standing for 10min. Then, the battery is discharged to 2.0V with a constant current of 0.1C, and the cut-off current is 0.05C. The first charge and discharge capacity during the charge and discharge process is recorded and the first coulomb efficiency is calculated. ② A cycle test is carried out at room temperature 25℃±2℃, charging to 4.0V with a constant current of 1C, the cut-off current is 0.05C, and the battery is left standing for 10min. Then, the battery is discharged to 2.0V with a constant current of 1C, the cut-off current is 0.05C, and the battery is left standing for 10min. This is a charge and discharge cycle. The discharge capacity after 100 and 300 cycles is recorded and the cycle capacity retention rate is calculated.

[0068] Table 1

[0069]

[0070] It can be seen from the results in Table 1 that compared with the blank example, the positive electrode sodium supplement Na prepared in Examples 1 to 4 x Fe y Ni z The gas production of O4@C increased by about 6-18%, while the gas production of the reference positive electrode sodium supplement prepared in Examples 1-4 increased by about 30-40%. x Fe y Ni z The gas production of O4@C is less than that of the reference positive electrode sodium supplement in the comparative example, indicating that the positive electrode sodium supplement Na x Fe y Ni zO4@C has the advantage of low gas production when used in sodium ion batteries. It can be seen from the results of Example 1 and Comparative Examples 1 and 2 that when the positive electrode sodium supplement does not contain iron and nickel elements at the same time, its gas production is greater than that of Example 1, and the discharge specific capacity, the first coulomb efficiency, the discharge specific capacity after 100 and 300 cycles and the capacity retention rate are all worse than those of Example 1. It can be seen from the results of Example 1 and Comparative Example 3 that when no organic solvent (fat-soluble solvent) is used in the preparation process, its gas production, discharge specific capacity, first coulomb efficiency, discharge specific capacity after 100 and 300 cycles and capacity retention rate are all worse than those of Example 1. It can be seen from the results of Example 1 and Comparative Example 4 that when no carbon source (glucose) is used in the preparation process, its gas production, discharge specific capacity, first coulomb efficiency, discharge specific capacity after 100 and 300 cycles and capacity retention rate are all worse than those of Example 1.

[0071] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A positive electrode sodium supplement Na x Fe y Ni z The preparation method of O4@C is characterized in that: The preparation method of the positive electrode sodium supplement comprises the following steps: S1. a sodium source, an iron source, a nickel source, and an organic solvent are subjected to a first mixing treatment and then filtered, and then a precursor mixture obtained after separating the organic solvent is subjected to a first calcination treatment to obtain a compound NFNC; S2. the compound NFNC obtained in step S1 and a carbon source are subjected to a second mixing treatment and then subjected to a second calcination treatment to obtain a positive electrode sodium supplement Na x Fe y Ni z O4@C, where x:y:z=(2~4):(0.5~2):

1.

2. The positive electrode sodium supplement Na according to claim 1 x Fe y Ni z The preparation method of O4@C is characterized in that: The positive electrode sodium supplement Na x Fe y Ni z The Dv50 particle size of O4@C is 0.5~3μm.

3. The positive electrode sodium supplement Na according to claim 1 x Fe y Ni z The preparation method of O4@C is characterized in that: The molar ratio of the sodium source, iron source and nickel source is (2-5):(0.5-3):1; preferably, the ratio between the mass of the sodium source, iron source and nickel source and the volume of the organic solvent is 1kg:(0.4-0.7)L.

4. The positive electrode sodium supplement Na according to claim 1 x Fe y Ni z The preparation method of O4@C is characterized in that: The sodium source is selected from at least one of sodium oxide, sodium peroxide, sodium carbonate, sodium hydroxide, sodium chloride, sodium nitrate and sodium oxalate; Preferably, the iron source is selected from at least one of ferrous sulfate, ferrous phosphate, ferrous carbonate, ferric chloride and ferric nitrate; Preferably, the nickel source is selected from at least one of nickel oxide, nickel hydroxide, nickel sulfate, nickel oxalate, sodium nitrate and nickel chloride; Preferably, the organic solvent is a fat-soluble solvent; Preferably, the fat-soluble solvent is selected from at least one of ether, petroleum ether, kerosene, hexane, heptane and carbon tetrachloride.

5. The positive electrode sodium supplement Na according to claim 1 x Fe y Ni z The preparation method of O4@C is characterized in that: The mass ratio of the compound NFNC to the carbon source is 1:(0.3-0.4); preferably, the carbon source is selected from at least one of glucose, sucrose, asphalt, cellulose and citric acid.

6. The positive electrode sodium supplement Na according to claim 1 x Fe y Ni z The preparation method of O4@C is characterized in that: In step S1, the first mixing treatment is carried out in the following manner: a sodium source, an iron source, a nickel source, and an organic solvent are placed in a ball mill for ball milling; preferably, the conditions for the ball milling treatment include: a rotation speed of 300 to 400 rpm and a time of 6 to 8 hours; preferably, in step S1, the conditions for the first calcination treatment include: a temperature T1 of 350 to 400°C and a holding time t1 of 3 to 5 hours.

7. The positive electrode sodium supplement Na according to claim 1 x Fe y Ni z The preparation method of O4@C is characterized in that: In step S2, the second mixing treatment is performed in the following manner: placing the compound NFNC and the carbon source in a fusion coating machine for coating treatment; preferably, the coating treatment conditions include: a rotation speed of 500 to 800 rpm and a time of 2 to 3 hours.

8. The positive electrode sodium supplement Na according to claim 1 x Fe y Ni z The preparation method of O4@C is characterized in that: In step S2, the conditions of the second calcination treatment include: temperature T2 is 900-1100°C, and holding time t2 is 4-6h.

9. The positive electrode sodium supplement Na prepared by the method according to any one of claims 1 to 8 x Fe y Ni z O4@C.

10. The positive electrode sodium supplement Na according to claim 9 x Fe y Ni z Application of O4@C in sodium-ion batteries.

Citation Information

Cited By

  • Battery additive and preparation method thereof, alkali metal ion battery positive pole piece and battery application

    CN120565681A